Application of Orem's theory for promotion of self-care behaviors of pregnant women at risk for preterm delivery: A clinical trial - Seyedeh Mahboobeh Rezaeean; Zahra Abedian; Robab Latifnejad Roudsari; Seyed Reza Mazloom; Salmeh Dadgar (Mashhad University of Medical Sciences, 2017)
Introduction: One of the most widely used theories in the field of self-care is the Orem's theory. According to this theory, patients can recover more quickly and holistically if they carry out their own self cares to the best of their ability. This study was performed with aim to investigate the application of Orem's theory for promotion of self-care behaviors of pregnant women at risk for preterm delivery. Methods: This clinical trial was done on 176 pregnant women at 24-26 gestational week at risk for preterm delivery who referred to health centers of Mashhad University of Medical Sciences in 2015-2016. The research tools included Holbrook risk-scoring for preterm labor questionnaire, demographic and obstetric questionnaire and Hart prenatal care actions scale. According to Holbrook risk-scoring for preterm labor questionnaire, the women who had inclusion criteria were selected. According to Hart prenatal care actions scale, the educational needs of intervention group and self-care behaviors were evaluated. Data were analyzed by SPSS software (Version16), and repeated measures ANOVA, Chi-square, Fisher exact and Mann-Whitney U tests. P<0.05 was considered significant. Results: The mean score of prenatal self-care was not significantly different in intervention and control group before educational intervention (P=0.899). But one week (P<0.0001) and two weeks (P<0.0001) after educational intervention and also in postpartum period (P<0.0001), the mean score of prenatal self-care was higher in intervention group compared to control group. Conclusion: The educational intervention based on Orem's theory is recommended to increase the prenatal self-care behaviors of pregnant women at risk for preterm delivery, identifying and training the prenatal self-care based on Orem's theory for women at risk for preterm birth in health care centers.